Appraisal of species composition and ecology of Drosophilids in the Lower Swat Valley, Pakistan - Rahman, Hamid Ur; Hadi, Gulalai (International Journal of Applied and Experimental Biology, 2025)
The drosophilid fauna of Pakistan remains largely understudied with numerous cities in the country yet to be thoroughly surveyed. This study aimed to investigate the drosophilid fauna of tehsil Babuzai in the Lower Swat Valley, Pakistan. The aerial net was used to collect flies from ten distinct locations within the tehsil. The specimens underwent dry preservation and subsequently analyzed using a digital microscope. Five distinct species were identified, all classified into two distinct genera within the family Drosophilidae. The taxa mentioned include Drosophila melanogaster, Drosophila immigrans, Drosophila willistoni, Drosophila hydei, and Zaprionus indianus. The present study reports that D. melanogaster exhibits a wider distribution than that of Z. indianus. The subsequent species in the distribution sequence was D. willistoni, whereas D. hydei and D. immigrans exhibited equivalent distribution patterns. The daily study of the flies’ habitat ecology revealed that their population peaked during low temperatures and high humidity. Dipteran insects were gathered from diverse fruit sources, and it was noted that they exhibited no preference for specific hosts. Drosophila melanogaster and D. immigrans were widely distributed and documented in all surveyed areas of Pakistan. The three remaining species showed a non-cosmopolitan distribution, and their inclusion in the present study indicates that the Swat Valley possesses favorable climatic conditions for their proliferation.